2018
DOI: 10.1186/s12903-018-0582-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of edentulism and their related factors in Indonesia, 2014/15

Abstract: BackgroundLittle information exists about the loss of all one’s teeth (edentulism) among older adults in Indonesia. The aim of this study was to investigate the prevalence of edentulism and associated factors among older adults in Indonesia.MethodThis study examines the self-reported prevalence of edentulism and associated factors among older adults (50 years and older) in a cross-sectional national study using the Indonesia Family Life Survey IFLS-5, 2014/15. The community-based study uses a multi-stage strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 59 publications
4
32
1
8
Order By: Relevance
“…Therefore, when we analysed oral health, a higher rate of edentulism is signi cantly observed among institutional residents. Earlier studies found similar results in Spanish, Indonesian and Brazilian elderly [26,27,28]. Similarly to tropical country, this nding can be attributed to unhealthy behaviours and attitudes towards dental care in Morocco.…”
Section: Health Characteristics and Nutritional Statussupporting
confidence: 75%
“…Therefore, when we analysed oral health, a higher rate of edentulism is signi cantly observed among institutional residents. Earlier studies found similar results in Spanish, Indonesian and Brazilian elderly [26,27,28]. Similarly to tropical country, this nding can be attributed to unhealthy behaviours and attitudes towards dental care in Morocco.…”
Section: Health Characteristics and Nutritional Statussupporting
confidence: 75%
“…In all, after written, informed consent was obtained, 2630 individuals 60 years and older were included with complete frailty measurements. The study response rate was above 90% [24][25][26].…”
Section: Study Design and Participantsmentioning
confidence: 81%
“…Cross-section analysis weights were applied "to make the IFLS-5 sample representative of the 2014 Indonesian population in the study provinces." [24][25][26]. Both the 95% confidence intervals and p-values were adjusted, taking the complex survey design of the study into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations